1993
DOI: 10.1093/ajcn/57.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B-12, vitamin B-6, and folate nutritional status in men with hyperhomocysteinemia

Abstract: We measured the vitamin B-6, vitamin B-12, and folic acid nutritional status in a group of apparently healthy men (n = 44) with moderate hyperhomocysteinemia (plasma homocysteine concentration > 16.3 mumol/L). Compared with control subjects (n = 274) with normal plasma homocysteine (< or = 16.3 mumol/L) concentrations, significantly lower plasma concentrations of pyridoxal-5'-phosphate (P < 0.001), cobalamin (P < 0.001), and folic acid (P = 0.004) were demonstrated in hyperhomocysteinemic men. The prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
162
0
5

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(173 citation statements)
references
References 40 publications
6
162
0
5
Order By: Relevance
“…Using a daily combined vitamin supplement containing 1000 mg folic acid, 12.2 mg vitamin B 6 , and 0.4 mg vitamin B 12 for six weeks in mild hyperhomocysteinemic men, demonstrated that high plasma homocysteine levels can be normalised. Doubling the vitamin doses for two weeks did not result in a further decrease in homocysteine levels (Ubbink et al, 1993a). Using the combined supplement (1000 mg folic acid, 12.2 mg vitamin B 6 , and 0.4 mg vitamin B 12 ), Ubbink and co-workers showed that some mild hyperhomocysteinemic men require only temporary vitamin supplementation to obtain long-term normal plasma homocysteine levels: after 6 weeks of vitamin intervention the advice to include more folate-rich foods in the diet was suf®cient to maintain normal plasma homocysteine levels (`16.3 mmol/L) for at least 48 weeks.…”
Section: Con®dence Intervalmentioning
confidence: 81%
See 2 more Smart Citations
“…Using a daily combined vitamin supplement containing 1000 mg folic acid, 12.2 mg vitamin B 6 , and 0.4 mg vitamin B 12 for six weeks in mild hyperhomocysteinemic men, demonstrated that high plasma homocysteine levels can be normalised. Doubling the vitamin doses for two weeks did not result in a further decrease in homocysteine levels (Ubbink et al, 1993a). Using the combined supplement (1000 mg folic acid, 12.2 mg vitamin B 6 , and 0.4 mg vitamin B 12 ), Ubbink and co-workers showed that some mild hyperhomocysteinemic men require only temporary vitamin supplementation to obtain long-term normal plasma homocysteine levels: after 6 weeks of vitamin intervention the advice to include more folate-rich foods in the diet was suf®cient to maintain normal plasma homocysteine levels (`16.3 mmol/L) for at least 48 weeks.…”
Section: Con®dence Intervalmentioning
confidence: 81%
“…Reported normal plasma values in healthy blood donors ranged from 7.9±9.3 mmol/L (Green & Jacobsen, 1995). Values b16.3 mmol/L are commonly considered indicative of milk hyperhomocysteinemia (Ubbink et al, 1993a(Ubbink et al, , 1993b(Ubbink et al, , 1994, although others have used levels b13.6 mmol/L (Hall & Chu, 1990), b14 mmol/L (Selhub et al, 1993), and b15 mmol/L (Genest et al, 1991).…”
Section: Con®dence Intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…To compensate for the lack of red-cell specimens in our study, we measured serum homocysteine, which has been proposed as a sensitive indicator of functional folate deficiency that is distinguishable from low serum folate concentrations following shortterm decreases in dietary intake (Kang et al, 1987;Stabler et al, 1988;Ubbink et al, 1993;Jacob et al, 1994;O'Keefe et al, 1995). Our data show that the variability of serum homocysteine in the population was much narrower than that of folate, suggesting that homocysteine levels are more tightly regulated by metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of the vitamins folate, cobalamin and B-6 have been shown to be related to elevated levels of tHcy (Ubbink et al, 1993;Selhub et al, 1993). Coffee and nonnutritional factors such as cigarette smoking and exercise have also been shown to be associated with the tHcy level (Nyga Êrd et al, 1995;Nyga Êrd et al, 1997b) in a dose dependent manner, and we have recently observed that smoking, coffee drinking and low vitamin intake are associated with both an increase in mean tHcy level as well as a more skew tHcy distribution (Nyga Êrd, 1997c), suggesting that lifestyle factors may be important determinants of the tHcy level.…”
Section: Introductionmentioning
confidence: 99%